REAL-TIME PID LINE FOLLOWING ALGORITHM FOR ARROW-BOT - Mirza Asrofi; M. Aziz Muslim; Mochammad Fauzi B. Zakaria (Jurnal Mahasiswa TEUB, 2015)
Arrow-bot is a line following robot that have three infrared (IR) sensors and two direct current (DC) motors as configured for differential wheel drive. Its main controller is an ATmega328, which has Arduino UNO bootloader. All line following robots ideally should have a capability to follow the line with accurate, smooth and fast response. The easiest way, to create a line following algorithm is based on bang-bang controller that is providing the robot turn a fixed amount in a particular direction according to the line sensor. However, the robot movement is not smooth and accurate to follow the line. Therefore, it needs an efficient control system algorithm and in this project, the proportional-integral-derivative (PID) controller is used to improve the robot performance. In addition, a few approach has been studied to acquire more accuracy of line data either by using digital or analog sensor concept. Besides, a real-time operating system (RTOS) is used to produce logical and temporal correctness of PID calculation. This RTOS implementation relies on ChibiOS/RT library for AVR microcontroller. As a result, the Arrow-bot performs well when implement PID RTOS with analog sensors concept. In conclusion, the line following robot, Arrow-bot with PID algorithm has accurate, smooth, and fast response capability to navigate along the line compared to bang-bang controller algorithm.Key words-Robot,Line follower, RTOS, PID, ChibiOS.